THE ASSOCIATION OF SOD2 AND GST GENE POLYMORPHISM WITH THE RISK OF DEVELOPMENT AND PROGNOSIS OF PAPILLARY RENAL CELL CARCINOMA (Medicinski podmladak, 2022)
Introduction: Redox imbalance is an important factor in both carcinogenesis and progression of renal cell carcinoma. Many studies are focused on finding potential biomarkers that can aid in early detection, as well as in monitoring disease progression. Among the candidates are genes coding for antioxidant enzymes - superoxide dismutase 2 (SOD2) and glutathione S -transferase (GST).Aim: This study aims to assess the role of SOD2 and GST genes polymorphisms in as risk biomarkers for papillary renal cell carcinoma (pRCC), along with their impact on the survival of these patients. Materials and methods: This study included 39 patients and 336 controls. SOD2 (rs4880), GSTA1C69T, GSTM1, GSTT1, and GSTP1 (rs1695) polymorphisms were determined by appropriate PCR methods. 8-hydroxy-2′-deoxyguanosine (8-OHdG) and benzo(a)pyrene diol epoxide (BPDE)-DNA adducts plasma level was measured by ELISA method. The effect of the polymorphisms on postoperative prognosis was examined using the available survival data.Results: There was no significant difference in the distribution of SOD2, GSTA1, GSTM1, and GSTT1 gene variants between patients and controls (p > 0.05). However GSTP1 variant (GSTP1 * IleVal + ValVal) genotype was statistically significantly more frequent in patients compared to controls (p < 0.05). Similarly, carriers of GSTP1 variant genotype were at significantly higher risk of developing carcinoma compared to carriers of GSTP1 reference genotype (OR = 16.103, 95% IP = 2.036 - 127.398). There was no association between the level of both 8-OHdG and BPDE-DNA adducts, and different genotypes (p > 0.05). The investigated polymorphisms did not show any prognostic significance (p > 0.05).
Keywords: Keywords: papillary renal cell carcinoma, SOD2, GST, risk, survival